Metabolic and ventilatory response to cross-country skiing classical and double arm poling exercise - Faria, I. E.; Faria, E. W.; Parker, D. (The Journal of Sports Medicine and Physical Fitness, 1996)
Nordic skiers place great emphasis on upper body endurance. Therefore, the purpose of this study was to compare oxygen uptake (VO2), minute ventilation (VE), tidal volume (VT), breath frequency (fB), heart rate (HR), and ventilatory anaerobic threshold (Tvan) responses to upper body classical poling (CP) and double poling (DP). Sixteen male master class cross-country ski racers performed DP and CP at similar incremental power outputs at 45 strokes/min on a modified Biokinetic swim bench variable-resistance arm ergometer. Leg VO2peak was measured during a Monark bicycle ergometer graded exercise test. Mean CP VO2peak was 34.8 +/- 9.0 ml kg-1 min-1 compared to 40.3 +/- 10.5 ml.kg-1 for DP (p < 0.05). CP and DP VO2peak was 70 +/- 3.4% and 81 +/- 3.8% respectively of the bicycle test VO2peak. DP VO2peak, and HR peak were significantly (p < 0.05) higher than for CP. CP Tvan appeared at 30.1 +/- 6.9 ml.kg-1.min-1 or 86 +/- 3.2% of CP VO2peak and DP Tvan occurred at 36.6 +/- 9.0 ml.kg-1.min-1 or 92 +/- 3.6% of DP VO2peak (p < 0.01). HR at Tvan was significantly higher for DP than for CP (< 0.05). Values for VT, fB, and VE measured at Tvan for both arm exercise modes were not significantly (p > 0.05) different. At submaximal exercise values for VO2, and HR were significantly different between the arm exercise modes. It is concluded that the mechanisms responsible for these observations may be increased active upper body muscle mass involvement for DP and that Tvan adaptations occur specifically to the exercise mode and recruited muscle groups.